Smart Door Lock System Using IOT - Aashi Gupta; Abhay Sharma; Aaryan Arora; Smita Bisht (International Journal of Satellite Remote Sensing, 2024)
The Internet of Things (IoT) represents a revolution in the way we interact with technology and the world around us. It incorporates a network of interconnected devices, sensors, and systems that collect, share, and analyze information to be effective, enhance decision-making, and improve every aspect of our lives. This content aims to provide an indepth look at the evolution, current state and future potential of the Internet of Things. The evolution of the Internet of Things can be traced to the convergence of various technological advances, such as ubiquitous connectivity, sensor miniaturization, and the spread of cloud computing. These advances have expanded IoT from healthcare and transportation to agriculture and manufacturing. The emergence of the Internet of Things (IoT) devices, making it easier to create smart, connected devices. Among these innovations, the development of smart door locks is a major advancement in home security and access control. This summary provides an overview of the design, functionality and benefits of smart door locks powered by IoT technology, Smart door lock systems combine door locking systems with IoT-enabled devices such as sensors, actuators and connectivity modules. These products work together via a smartphone, tablet or web interface. The central access point provides remote access, monitoring and control functions. has changed the way we interact with everyday.
Keywords: Arduino; Buzzer; Internet of Things; security; smart door lock system